2012
DOI: 10.1089/cbr.2012.1245
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Induces the Apoptosis of Human Osteosarcoma Cells In Vitro and In Vivo via the Regulation of Mitogen-Activated Protein Kinase Pathways

Abstract: To examine the antitumor effects of gallic acid (GA) on osteosarcoma, two human osteosarcoma cell lines U-2OS and MNNG/HOS were treated by GA and subjected to cell proliferation and apoptosis assays. In addition, MNNG/HOS xenograft tumors were established in nude BALB/c mice to evaluate the anticancer capacity of GA in vivo. The results showed that GA inhibited the proliferation and induced the apoptosis of osteosarcoma cells, accompanied by the upregulation of p-38 activation and the downregulation of c-Jun N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 40 publications
4
40
0
Order By: Relevance
“…Cucurbitacin B exposure caused marked activation and enhanced expression of caspase-9, -8 and -3. These observations suggest that cucurbitacin B induces apoptosis via the intrinsic pathway, which is in accordance with a previous study using chemotherapeutic drugs as gallic acid (54). Furthermore, Liu et al (55) reported that the majority of chemotherapeutic drugs were able to induce apoptosis through the intrinsic mitochondrial pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Cucurbitacin B exposure caused marked activation and enhanced expression of caspase-9, -8 and -3. These observations suggest that cucurbitacin B induces apoptosis via the intrinsic pathway, which is in accordance with a previous study using chemotherapeutic drugs as gallic acid (54). Furthermore, Liu et al (55) reported that the majority of chemotherapeutic drugs were able to induce apoptosis through the intrinsic mitochondrial pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have suggested that Akt, p38, JNK, and ERK1/2 cascades have critical roles in the induction of apoptosis [30,31]. Therefore, to elucidate the mechanisms underlying IUA-induced apoptosis, the levels of Akt, p-Akt, p38, p-p38, JNK, p-JNK, ERK1/2, and p-ERK1/2 were analyzed by Western blotting in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar fashion, ferulic acid at a dose of 10, 30 and 50 mg/kg body weight inhibited the melanoma tumor development in nude mice [88]. The trihydroxy benzoic acid (gallic acid at 0.3 and 1.0%) also inhibited the growth of osteocarcinomas in xenograft mice models [89]. The data showed a significant reduction in the tumor volume from 2392.99 mm 3 in control group to 1896.34 mm 3 and 1476.55 mm 3 in the treated groups [89].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The trihydroxy benzoic acid (gallic acid at 0.3 and 1.0%) also inhibited the growth of osteocarcinomas in xenograft mice models [89]. The data showed a significant reduction in the tumor volume from 2392.99 mm 3 in control group to 1896.34 mm 3 and 1476.55 mm 3 in the treated groups [89]. Another study also demonstrated the anti-tumor potential of gallic acid.…”
Section: In Vivo Studiesmentioning
confidence: 99%